Sucrose and sodium but not caffeine content influence the retention of beverages in humans under euhydrated conditions - Maughan, R. J.; Watson, P.; Cordery, P. A. A.; Walsh, N. P.; Oliver, S. J.; Dolci, A.; Rodriguez-Sanchez, N.; Galloway, S. D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
This study systematically examined the influence of carbohydrate (sucrose), sodium, and caffeine on the fluid retention potential of beverages under euhydrated conditions, using the beverage hydration index method. Three cohorts, each of 12 young, healthy, active men, ingested 1 L of beverages containing four different concentrations of a single component (sucrose, sodium, or caffeine) in a double-blind, crossover manner. Urine output was collected for the subsequent 4 hr. Cumulative urine output was lower and net fluid balance was higher after 10 and 20% sucrose beverages than 0 and 5% sucrose beverages (p < .05), and after 27 and 52 mmol/L sodium beverages than 7 and 15 mmol/L sodium beverages (p < .05). No difference in urine output or net fluid balance was apparent following ingestion of caffeine at concentrations of 0-400 mg/L (p = .83). Consequently, the calculated beverage hydration index was greater in beverages with higher sucrose or sodium content, but caffeine had no effect. No difference was observed in arginine vasopressin or aldosterone between any trials. These data highlight that the key drivers promoting differences in the fluid retention potential of beverages when euhydrated are energy density, likely through slowed fluid delivery to the circulation (carbohydrate content effect), or electrolyte content through improved fluid retention (sodium content effect). These data demonstrate that beverage carbohydrate and sodium content influence fluid delivery and retention in the 4 hr after ingestion, but caffeine up to 400 mg/L does not. Athletes and others can use this information to guide their daily hydration practices.